Karyotype evolution in Curimatidae (Teleostei, Characiformes) from the Amazon region. II. Centric fissions in the genus Potamorhina - Feldberg, Eliana; Porto, Jorge Ivan Rebelo; Nakayama, Celeste Mutuko; Bertollo, Luiz Antônio Carlos (Genome, 1993)
Using cytogenetic analysis following Giemsa staining, nucleolar organizer region (NOR) staining, and C-banding, three distinct karyotypes in three species of curimatids belonging to the fish genus Potamorhina were identified: 2n = 54/44 M + 10 SM (P. pristigaster), 2n = 56/52 M + 2 SM + 2 ST (P. latior), and 2n = 102/2 M + 2 SM + 98 A (P. altamazonica). A 2n = 54 was considered to be the ancestral diploid number and the different karyotypes were probably the result of centric fissions. Both the NOR pattern and constitutive heterochromatin pattern are species specific.
Keywords: Animals Cell; Fish; Karyotype Evolution; Nonhuman; Phylogeny; Robertsonian Chromosome Translocation; Animalsia; Characiformes; Curimatidae; Potamorhina; Potamorhina Latior; Pristigaster; Robertsonia; Teleostei